Strategi Komunikasi dan Relationship Marketing dalam Meningkatkan Kepercayaan Publik pada Lembaga Nonprofit: Studi Kasus Dompet Dhuafa - Akhmad Wahidin; Dwi Rabita (IAI Nasional Laa Roiba Bogor, 2026)
Nonprofit institutions play a strategic role in supporting social development through various community empowerment, humanitarian service, education, health, and poverty alleviation programs. In Indonesia, the development of philanthropic institutions has increased significantly alongside growing public awareness of social and humanitarian activities. One rapidly growing nonprofit institution is Dompet Dhuafa, an Islamic philanthropic organization engaged in managing zakat, infak, alms, and endowment (wakaf) funds. Dompet Dhuafa's success in building public trust is determined not only by its ability to collect social funds but is also influenced by organizational communication strategies and relationship marketing applied to build long-term relationships with stakeholders. This study aims to analyze organizational communication strategies, the application of relationship marketing, and stakeholder management in increasing public trust toward Dompet Dhuafa as a nonprofit institution. Furthermore, this study aims to identify various challenges faced by the organization in maintaining public legitimacy amidst increasingly competitive philanthropic institutions. This research employs a qualitative approach using the literature study method. The qualitative approach was chosen because this study seeks to profoundly understand social phenomena and organizational strategies through the interpretation of various data obtained. Research data were gathered through the collection and analysis of various secondary sources, such as scientific journals, academic books, organizational annual reports, and information derived from Dompet Dhuafa's official website. The results of the study indicate that digital communication strategies, organizational report transparency, and emotion-based relationship marketing have a major influence on increasing donor loyalty and public participation. The utilization of social media, digital campaigns, and storytelling are considered capable of strengthening the organization's image and building emotional relationships with the public. Additionally, the application of stakeholder theory is an important factor in maintaining organizational relationships with donors, beneficiaries, the government, volunteers, media, and the community. However, this study also highlights various challenges faced by nonprofit institutions, such as the dominance of donor interests over beneficiaries, the potential for symbolic exploitation in social campaigns, internal communication barriers due to organizational complexity, and limited evaluations of long-term program impacts. Therefore, this research is expected to provide theoretical and practical contributions to developing nonprofit organizational management and communication strategies that are more participatory, transparent, adaptive, and sustainable.